Implementation of a self-management programme: recruitment strategies in five European countries. (30th September 2020) - Doñate-Martínez, A; Pisano-González, M; Boone, A L; Vázquez, R; Peñacoba, D; Valsecchi, V; Zora, S; Tan, S S; Baker, G; Garcés, J
Abstract: Introduction: The Chronic Disease Self-Management Programme (CDSMP) has been successfully implemented in over 30 countries worldwide, demonstrating its effectiveness and cost savings to healthcare systems. The CDSMP aims at people with any chronic condition and caregivers, but it has not targeted specific vulnerable populations at different sites simultaneously. In this sense, this study presents the recruitment strategies to involve vulnerable populations in the CDSMP framed under the EU-funded project EFFICHRONIC (ref.: 738127). Methods: The CDSMP was implemented in five countries (Spain, Italy, France, the Netherlands and the United Kinkdom) approaching several vulnerable target groups. The programme consists of strictly scripted group sessions during 6 weeks imparted by previously trained monitors. EFFICHRONIC recruitment was performed in 3 consecutive steps combining population-based and individual strategies: i) development of vulnerable maps to detect areas with higher vulnerability; ii) creation of alliances with different actors; and iii) identification of end-users. Results: Over 234 leaders were trained distributed over the five sites and 237 workshops with end-users were organized following the recruitment strategies. The average number of engaged participants per workshop was 13. In total, 2, 962 vulnerable persons were engaged and 2, 177 finalized the programme, meaning a drop-out rate of 25%. The sample was composed of ethnic minorities, immigrants, refugees, older people living alone or in institutions, people with few economic resources or living in therapeutic communities, inmates and members of different kinds of associations. Discussion: The strategic coordination at loco-regional level between multidisciplinary stakeholders has been a key success factor to obtain maximum recruitment. The activation of different strategies simultaneously optimized the project results approaching a wide variety of end-users and communities. Key messages: Stakeholder engagement is crucial to identify and recruit vulnerable individuals in need of support for the management of their chronic conditions. Recruitment strategies must be adapted to each specific context and culture to achieve relevant adherence levels and benefits.